Exploring the multicultural design of Malaysian Ang-Pow - Ling, Siek Hwee * (2021)
Malaysia is a multicultural and multiethnic moderate Islamic country 31 million people with three main ethnic groups: Malays, Chinese, and Indians; Under Malaysian constitutional law, all Malays are Muslims, the largest ethnic group with 50.4% of the population, Malaysian Chinese is at 22.6%. Each ethnic group has their respective festive season celebrations such as Hari Raya Aidilfitri, is the day after the holiest period in the Islamic year when Muslims rejoice. Chinese New Year, to Chinese over all the world, it signifies a prosperous new year and Deepavali, is the festival of lights, signifies light over darkness. During Hari Raya festive season, Malaysian Muslims devote ‘duit raya’ (cash gifts) to children and old folks. During Chinese New Year, Chinese people give each other ‘Ang-Pow’ (red envelope), a monetary gift that symbolizes good fortune and prosperity. For Deepavali, money and gift were not presented in the old days but due to influences and rituals from other cultures, monetary gifts are distributed by family members. Festive celebrations often involve distinctly cultural designs which help to share traditional virtues and conveying information among people regardless of ethnicity or religion. This paper attempts to outline how the Malay’s green Ang-Pow and Indian’s purple Ang-Pow in Malaysia subverted the Chinese’s Ang-Pow by not transforming its original purpose. The designs printed on different Ang-Pows have certain design criterion which reveals the unique cultures in Malaysia. This paper adducted the elements of Cultural Markers Method set by four graphic design industry’s experts to analyze the content and identify the embedded cultural characteristics in a total of 99 Ang-Pows; thus six significant elements of the cultural factors according to their layout, logo, language, typography, colour, and images were identified. This was followed by a t-test to determine significant differences that reflect the graphic preferences of these ethnic groups and the uniqueness of Malaysian culture. This study also demonstrates that the existence of a design ‘platform’ (the space for the composition of the visual elements) creates opportunities to showcase and drive the creativity and aesthetics of different ethnic cultures. The modification of visual images on Chinese Ang-Pow to graphics from other ethnic groups has positively facilitated a flexible strategy that proves it is well accepted and widely used by Malaysian society. Based on the analyses of the cultural marker identification, designers of green and purple Ang-Pow should prioritize horizontal layout for words and texts to reveal racial identity. Malays seem to prefer the ability to select their preferred Ang-Pow designs instead of using those with merchant logos. Since Malays hold the majority in Malaysia, graphic designers can extend the market in this direction.